Penerapan Aplikasi Android E-Payment dan Pemesanan Layanan Pujasera - Subari, Subari; Ramadhan, Adrian (Jurnal Teknologi dan Manajemen Informatika, 2022)
Pujasera or Multi-purpose Snack Center is an area where food and drinks are served or enjoyed by buyers which consist of many variations of sellers divided into outlets, booths, or stalls. In general, each of these outlets conducts transactions directly with buyers, both choosing orders, serving food, and paying. This raises several problems, including queue numbers that are no longer in order and table numbers that are not well-coordinated, and the occurrence of queues of buyers. The purpose of this study is to design an Android-based application with e-payment and ordering service features at the food court so that it is expected to minimize obstacles and errors that occur. The payment mechanism is also carried out virtually with the existence of e-payments to make it easier for buyers and store owners. The features provided start from the deposit and balance refunds, and other related services so that they don't have to queue and don't have to carry cash. This implemented system can provide convenience and comfort to buyers and store owners, the application works well and is integrated to facilitate ordering and payment services to be more transparent and more informative. The percentage of interpretation evaluation is categorized as very feasible, with the results of the evaluation of application users with an interpretation level of 90%.